PENGUATAN KETAHANAN NILAI KEAGAMAAN, KEBUDAYAAN, DAN SPIRITUALITAS MELALUI PABBAJJĀ DAN UPASAMPADĀ - Burmansah, Burmansah; Andriyaningsih, Ayu; Sutiyono, Sutiyono; Saputri, Vike Aprilianin Marwintaria; Suryanadi, Juni; Ardianto, Hendri (PT. Jurnal Center Indonesia Publisher, 2025)
This Community service program aims to strengthen the Buddhist community's religious, cultural, and spiritual values by implementing Pabbajjā and Upasampadā at Muaro Jambi Temple, a historic Buddhist heritage site in Indonesia. The program is motivated by the need for a learning medium integrating Buddhist teachings with direct experience in a religious and cultural environment. The implementation adopted a participatory and collaborative approach, engaging participants particularly university students in ritual activities, Dharma discussions, and the practice of moral precepts (sīla). The selection of Muaro Jambi Temple also served as a strategy to revitalize the site’s function as a center for spiritual cultivation and cultural preservation. The results indicate a significant improvement in participants’ understanding of the Dharma, adherence to moral precepts, and awareness of the importance of Buddhist cultural heritage. The program fostered the development of religious character and cultural identity, enhancing participants’ commitment to preserving the noble values of Buddhism within the local context. Furthermore, it opened opportunities for the development of history-based religious tourism. In conclusion, this PKM effectively integrates religious education, character building, and cultural preservation. Its sustainability requires multi-stakeholder support to ensure that the values, history, and spirituality of the Nusantara heritage are preserved authentically and meaningfully.